Failed Switching off in the MIBI-Parathyroid Scintigraphy in a Dialyzed Patient with Secondary Hyperparathyroidism Responsive to Cinacalcet Therapy - Piergiorgio Bolasco; Alessandra Serra; Maurizio Loi; Andrea Galfré; Mario Piga (International Journal of Endocrinology)
The aims of your case report is to show the predictivity of Tc99m-sestamibi (MIBI) scintigraphy and doppler ultrasound imaging on secondary hyperparathyroidism (SHPT) in a patient responsive to calcimimetic treatment. Moreover, it has been reported that calcimimetic has great potential in reducing the volume of the parathyroid gland. On the other hand, the MIBI scintigraphy is considered a crucial diagnostic procedure to monitor the response to therapy in terms of turnover and cellular metabolism; whereas, ultrasound to monitor the volume variation in response to treatment. It is described the case of a 73-year-old man on hemodialysis from 1995 for ESRD. Within 2 years the patient gradually developed SHPT with progressively increased iPTH up to 1,000 ρg/ml. The ultrasound, highlighted the presence of two parathyroid hyperplasia, confirmed by scintigraphy, showing focal increase uptake of sestamibi in the same anatomical areas. As a result of the patient's refusal to perform a parathyroidectomy, cinacalcet, was administered (65 mg overage daily dose). After a year of treatment, there was a striking decrease of iPTH (from 1300 to 57 ρg/ml, −95%); but, on the contrary to expectations, this positive metabolic outcome, was not followed by parathyroid changes in ultrasound and scintigraphic findings.